(untitled) (Marketing Journal, 2025)
This article studies the current issues of increasing the competitiveness of small business entities and improving the management mechanism. Today, small business is considered a key tool in economic development, ensuring employment of the population, soci o-economic development of regions and increasing the stability of the economy. At the same time, there is a need to increase competitiveness in the activities of small business entities and improve the management system in accordance with modern requiremen ts. The study was conducted on the example of the Namangan region, the current state of small business entities in the region, the main factors limiting their development were identified, and effective measures were proposed to combat them. In this regard, state programs, legal and regulatory documents aimed at the development of small businesses were analyzed, and ways to increase their efficiency were identified. The article develops practical recommendations on improving management mechanisms based on in novative solutions, rational use of financial resources and increasing human resources. The results are of great importance in increasing the economic efficiency of small business entities and sustainable development of the regional economy.